Genetic and Morphological Variation of the Redbelly Yellow Tail Fusilier, Caesio cuning (Bloch, 1971) from the Nyamuk Waters, Karimunjawa Archipelago - Nining Nursalim; Agus Trianto; Ni Kadek Dita Cahyani; Nenik Kholilah; Galank Fad'qul Janarkho; Eko Hardianto; Subagiyo Subagiyo (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
Yellowtail fusilier, Caesio cuning (Bloch, 1971) is the main catch of fishermen on the Nyamuk Island, Karimunjawa. C. cuning also has a unique character in the form of different eye color, white, red, and white-red. These differences were raise question whether the eye colors will be differentiated the morphology, and the genetic diversity of C. cuning. This research aims to study the biodiversity of C. cuning caught by fishermen on Nyamuk Island, Karimunjawa, based on their morphology, and molecular using mtDNA control region gene marker.  This study also wanted to test, if different eye colors observed on the sample also reflected at the genetic level. A unique thing was found in morphological observations in the form of eye colors in C. cuning (white, red and white-red). Measurements of 19 morphometric characters were conducted on 44 samples directly in the field. Twenty four  (24) samples with three different eye colors were selected for molecular assay of locus control region mtDNA in the laboratory. Morphological analysis showed the total length of 44 samples of C. cuning ranged from 15-29.4 cm. The total length of white eye color ranged from 15-29.4 cm from 20 samples, red-eye color 17-26 cm from 20 samples and white-red eye color 22-24.6 from 4 samples. Molecular test showed that the fish observed was indeed C. cuning with a similarity of 97.07%-99.27% of NCBI data. The genetic distance C. cuning between individuals was 0-3%.  Genetic distance in the same eye color and different have the same value of 2%. Twenty haplotypes were obtained from 24 samples with high haplotypes diversity, values ranging from 0.978-1,000. The nucleotide diversity ranges from 0.019-0.021. There is no molecular difference between C. cuning with different eye colors.